Non-invasive analysis of faience necklace beads and scarabs from Late Bronze Age and Early Iron Age necropolises in southern Portugal - António M. Monge Soares; António P. Gonçalves; Luis C. Alves; Pedro Valério; Filipe Santos; Rui Monge Soares; Manuela de Deus (Trabajos de Prehistoria)
In this work, non-invasive techniques (XRD and microPIXE) were used to study 14 necklace beads associated with human inhumations from the Late Bronze Age (10th-9th century BC) hypogea of Monte da Ramada 1 (Aljustrel), from the Early Iron Age (7th-6th century BC) necropolises of Palhais (Beja), Montinhos 6 (Serpa) and Corte Margarida (Aljustrel), and a blue bead from the Orientalising settlement (8th century BC) of Quinta do Almaraz (Almada). Two scarabs were also analysed, one found in Palhais and the other at Corte Margarida. The results show that most of these small, high-value ornaments have a body of ground quartz covered by glaze. They are consequently classified as faience artefacts. In addition, specific colorants of the glazing mixture were recognised, namely metal ions such as those of copper for the blue/green glazes and of iron for the red/brown glazes.